Semiclassical Effective Hamiltonian For Coupled Electronic And Nuclear Optical Response - Meier, Torsten; Chernyak, V.; Tretiak, S.; Tsiper, EV..; Mukamel, S. (Condensed Matter Theories)

Die Dialektik der Globalisierung in Technik, Ökonomie, Politik und Kultur (The Dialectic of Globalization in Technology, Economy, Polity, and Culture) - Fuchs, Christian; Hofkirchner, Wolfgang (Online-Proceedings Jubiläumskongresses der Österreichischen Gesellschaft für Soziologie)

Nanometer Scale Lateral Structures of MOS Type Layers - Hilleringmann, Ulrich; Vieregge, T; Horstmann, JT (Proceedings Micro. tec)

Coherent dynamics of photoexcited semiconductor superlattices in homogeneous electric fields - Meier, Torsten; Kolbe, H.J.; Thränhardt, A.; Weiser, G.; Thomas, P.; Koch, S.W. (Physica E: Low-dimensional Systems and Nanostructures)
A microscopic many-body theory for the linear and nonlinear optical properties of semiconductor superlattices subjected to electric fields is presented. The approach has been used for the analysis of various processes related to the Bloch-oscillation dynamics of carriers in static fields and for investigating dynamical localization induced by alternating fields. It is shown that the theory describes very well experimental field-modulated absorption spectra of a strongly coupled superlattice. Furthermore, characteristic signatures, such as negative absorption in the short-pulse optical response of superlattices subjected simultaneously to static and alternating electric fields are predicted.

Propagation of Coulomb-Correlated Electron-Hole Pairs in Semiconductors with Correlated and Anticorrelated Disorder - Meier, Torsten; Thomas, P.; Varga, I.; Lemm, T.; Golub, J.E.; Maschke, K.; Koch, S.W. (physica status solidi (b))
Local ultrafast optical excitation of electron–hole pairs in disordered semiconductors provides the possibility to observe experimentally interaction-assisted propagation of correlated quantum particles in a disordered environment. In addition to the interaction driven delocalization known for the conventional single-band TIP-(two-interacting-particles)-problem the semiconductor model has a richer variety of physical parameters that give rise to new features in the temporal dynamics. These include different masses, correlated versus anticorrelated disorder for the two particles, and dependence on spectral position of excitation pulse.

Investigation of Disordered Semiconductor Quantum Wells by Coherent Excitation Spectroscopy - Meier, Torsten; Euteneuer, A.; Finger, E.; Stolz, W.; Thomas, P.; Koch, S.W.; Hofmann, M.; Rühle, W.W.; Hey, R.; Ploog, K.H. (physica status solidi (a))
First, we study coupling of excitons in different quantum-well islands by coherent excitation spectroscopy and find that excitons in different islands are not coherently coupled. Second, we investigate exciton and biexciton binding energies in inhomogeneously broadened (GaIn)As/Ga(PAs) multi quantum wells. A strong increase of the 1s–2s-splitting with increasing exciton localization is found, whereas the biexciton binding energy shows a very weak decrease with increasing localization.

Disorder-induced Dephasing in Semiconductors - Meier, Torsten; Weiser, S.; Möbius, J.; Euteneuer, A.; Mayer, E.J.; Stolz, W.; Hofmann, M.; Rühle, W.W.; Thomas, P.; Koch, S.W. (Physical Review B)
Microscopic calculations including energetic disorder and Coulomb correlations up to third order in the laser field are performed. The resulting four-wave-mixing signals show polarization-dependent dephasing induced by diagonal disorder. The correct modeling of this disorder-induced dephasing requires the proper inclusion of Coulomb correlations. The theoretical results are in good qualitative agreement with measurements performed on a variety of quantum-well samples.

"Denn die Lehre feiert auch, und die Feier lehret" - Prospekt einer liturgischen Didaktik - Schroeter-Wittke, Harald

Ahnung von der Predigt. Konturen homiletischer Didaktik - Schroeter-Wittke, Harald

Unterhaltung - Praktisch-theologische Exkursionen zum homiletischen und kultirellen Bibelgebrauch im 19. und 20. Jahrhundert anhand der Figur Elia - Schroeter-Wittke, Harald

"Czy to ty jestes, Eliaszu?" Migawka z homiletycznego wykorzystania tekstów o Eliaszu poczawszy od 1945 roku - Schroeter-Wittke, Harald (Eliasz. Zeszyty ewangelickiego katechtey Nr. 2)

Prophetie - Politik - Pädagogik. Beobachtungen zu den Elias-Homilien des Darmstädter Hofpredigers Ferdinand Bender - Schroeter-Wittke, Harald (Jahrbuch der Hessischen Kirchengeschichtlichen Vereinigung)

Mendelssohns "Elias" - Ein Bibliodrama zwische Kirche und Konzertsaal - Schroeter-Wittke, Harald (Theophonie. Grenzgänge zwischen Musik und Theologie)

Theophonie. Grenzgänge zwischen Musik und Theologie. Anke Martiny zum 60. Geburtstag

Hast du Töne? Zum Umgang mit Musik - Schroeter-Wittke, Harald (Leistungskurs Religion. Vorlesungen zur Kunst der Religionspädagogik)

Das Evangelische Gottesdienstbuch und die liturgische Didaktik - Schroeter-Wittke, Harald (Deutsches Pfarrerblatt)

Praktische Theologie für kreative Gemeindearbeit. Ein Überblick zur gegenwärtigen deutschen Praktischen Theologie - Schroeter-Wittke, Harald; Hauschildt, Eberhard; Lee, Young-Mi

Kirchentag als Kunstereignis - Vision bislang nicht ausgeschöpfter Möglichkeiten - Schroeter-Wittke, Harald (Kirchentag aktuell März 2000)

Analysis of disorder-induced dephasing - Meier, Torsten; Weiser, S.; Möbius, J.; Euteneuer, A.; Mayer, E.J.; Stolz, W.; Hofmann, M.; Rühle, W.W.; Thomas, P.; Koch, S.W. (International Quantum Electronics Conference)
A number of experiments yielded a polarization-dependent decay of the time-integrated four-wavemixing (TI-FWM). Often, the TI-FWM decays more rapidly for linear perpendicular than for linear parallel polarized incident pulses. It was suspected that this difference in the decay times is related to the inhomogeneous linewidth of the exciton, i.e. to disorder [1], On the other hand, it was demonstrated in a large number of recent publications, that the understanding of polarization-dependent FWM and pump-probe experiments following excitonic excitation requires the treatment of Coulomb correlations beyond the Hartree-Fock level. For not too strong disorder, these correlations still remain important and influence the nonlinear optical response [2]. A meaningful analysis of disorder effects thus has to include correlations.

Influence of correlations on intensity dependent excitonic absorption changes - Meier, Torsten; Koch, S.W.; Brick, P.; Ell, C.; Khitrova, G.; Gibbs, H.M. (International Quantum Electronics Conference)
Polarization dependent excitonic absorption changes have been studied recently for excitation with weak pump pulses [1]. It was shown, that for both resonant and off-resonant excitation even in the low-intensity χ(3)-limit many-body Coulomb correlations strongly contribute the optical response [1]. Here we investigate, how the coherent pump-induced absorption changes vary with the pump intensity, by analyzing the next higher, i.e. the fifth-order contributions.